Skrining Bakteri Asam Laktat dan Khamir Potensial Proteolitik Ekstraseluler dan Milk Clotting Activity Dari Ekstrak Dan Fresh Cheese Stroberi (Fragaria x ananassa Duch.) - Putri, Cindy Meylia; Rustama, Mia Miranti; Putranto, Wendry Setiyadi (Jurnal Teknologi Hasil Peternakan, 2024)
Fresh cheese is one of the popular cheeses, it can be eaten directly and is made without going through ripening with coagulation by rennet. Strawberries (Fragaria x ananassa) are known to have proteolytic enzymes and endophytic microbes. Fresh cheese produced with coagulant extract of strawberry fruit isolated the presence of LAB and yeast which have proteolytic and MCA activity. This research method is descriptive exploratory. The fresh strawberry cheese produced in this study was whitish red in color and had a fine texture. The total LAB of extract, fresh strawberry cheese, and pasteurized milk were respectively 1.9 x 104 CFU/mL and 1.8 x 104 CFU/g, 1.5 x 104 CFU/mL, while for yeast it was 5.2 x 105 CFU/mL and 6.4 x 104 CFU/g, 5.0 x 103 CFU/mL. In this study, 3 LAB isolates and 2 yeast isolates were found from strawberry extract and fresh cheese. BAL and yeast from isolates ES3, FS4, FS5, YFC1, and YES2 had proteolytic indices of 0.375, 0.125, 0.25, 1.625, and 1.25, respectively. The MCA value for each isolate was 203.44; 212.53; 205.13; 3.7; and 1.73 SU/mL. The BAL obtained was suspected to be from the genus Lactobacillus and yeast isolates suspected to be of the genus Saccharomyces and Debaryomyces.  In this study, BAL and yeast were found to have extracellular proteolytic potential and MCA.